Harnessing the role of mitogen-activated protein kinases against abiotic stresses in plants - Majeed, Yasir; Zhu, Xi; Zhang, Ning; ul-Ain, Noor; Raza, Ali; Haider, Fasih Ullah; Si, Huaijun (Frontiers in Plant Science, 2023)
Crop plants are vulnerable to various biotic and abiotic stresses, whereas plants tend to retain their physiological mechanisms by evolving erudite cellular regulation. To overcome the abiotic stresses, many defense mechanisms are induced in plants. One of these mechanisms is the mitogen-activated protein kinase (MAPK) cascade, a signaling pathway used in the transduction of extracellular stimuli into intercellular responses. This stress signaling pathway is activated by a series of responses involving MAPKKKs→MAPKKs→MAPKs, comprising of interacting proteins, and their functions depend upon the collaboration and activation of one another by phosphorylation. These proteins are key regulators of MAPK in various crop plants under abiotic stress conditions and also related to hormonal responses. It is revealed that in response to stress signaling, MAPK are characterized as multigenic families and elaborate the specific stimuli transformation as well as antioxidant regulation system. This pathway is directed by the framework of proteins and stopping domains privilege the relating associates with unique structure and functions. Early studies of plant MAPKs focused on their functions in model plants. Based on the results of whole-genome sequencing, many MAPKs have been identified in plants, such as Arbodiposis, tomato, potato, Alfalfa, popula, rice, wheat, maize, and apple. In this review article, we summarized the recent work on MAPKs response to abiotic stress and classification of MAPKs cascade in crop plants. Moreover, we highlighted the modern research methodologies such as transcriptomic, proteomics CRISPR/Cas technology, and epigenomic studies, which proposed, identified, and characterized the novel genes associated with MAPKs and their role in plants during stress conditions. This study also facilitates the future research on MAPKs cascade identification and function in crop plants under various stress conditions.